An Online Cross-Sectional Survey: Changes in Food Group Consumption on Complementary Feeding during COVID-19 Pandemic in Indonesia - Rahayu, Herwinda Kusuma; Hariawan, Muhammad Hafizh; Paratmanitya, Yhona; Herawati, Herni Dwi; Nuryani, Rindi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to assess the impact of COVID-19 pandemic on food group consumption of complementary feeding in Indonesia. Data were collected using online self-administered questionnaires on Indonesian mothers of children aged 6–23 months. The result showed that households with decreased ability to provide food during the COVID-19 pandemic tended to choose unhealthy food groups on complementary feeding. There were higher odds of unhealthy food consumption, such as sweetened beverages, including fruit juice (OR=3.181; 95% CI:1.788−5.657) and homemade drink with sweeteners (OR=1.652; 95% CI:1.034−2.641); sugar confection (OR=2.066; 95% CI:1.240−3.444); frozen treats (OR=2.270; 95% CI:1.400−3.681), baked or fried confection (OR=2.154; 95% CI:1.435−3.235); fried and salty foods (OR=1.633; 95% CI:1.059−2.517). Meanwhile, the odds of food group consumption which lower during COVID-19 pandemic mostly are animal source foods group, including yogurt (OR=0.297; 95% CI:0.161−0.548); yogurt drink (OR=0.253; 95% CI:0.138−0.464); cheese (OR=0.355; 95% CI:0.230−0.549); eggs (OR=0.675; 95% CI:0.461−0.991); fish or seafood (OR=0.409; 95% CI:0.279−0.600); organ meats (OR=0.304; 95% CI:0.180−0.512); meats (OR=0.339; 95% CI:0.225−0.511); and poultry (OR=0.339; 95% CI:0.225−0.511). However, effective strategy for enhancing complementary feeding quality during pandemic should be formulated.